(untitled) (Bangladesh Journal of Pharmacology, 2013)
NF-?B constitutively expresses in human pancreatic cancer cells and has been implicated in pancreatic tumorigenesis. Evodiamine, a bioactive alkaloid has been shown to possess antioxidant, anti-inflammatory and antitumor properties. In the present study, the anti-pancreatic cancer potential of evodiamine have been evaluated. Evodiamine effectively inhibited growth and induced apoptosis in PANC-1 cells in a dose-dependent manner. SN50 (NF-?Bp65 inhibitor) significantly increased the evodiamine-induced apoptotic cell death in PANC-1 cells, indicating that NF-?B is involved in evodiamine-induced apoptotic cell death. Furthermore, Western blot analysis showed that evodiamine inhibited the constitutive activation of NF-?Bp65, decreased the expression of anti-apoptotic protein Bcl-2, increased the expression of pro-apoptotic protein Bax and cleaved caspase-3 in PANC-1 cells in a dose-dependent manner. The present study suggests that evodiamine induces apoptosis in PANC-1 cells via NF-?Bp65 inhibition and apoptosis regulators modulation.